2018
DOI: 10.5506/aphyspolb.49.1781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Axialvector Doubly Heavy Tetraquark States with QCD Sum Rules

Abstract: In this article, we construct the diquark-antidiquark type current operators to study the axialvector Bc-like tetraquark states with the QCD sum rules. In calculations, we take the energy scale formula as a powerful constraint to choose the ideal energy scales of the QCD spectral densities and add detailed discussions to illustrate why we take the energy scale formula to improve the QCD sum rules for the doubly heavy tetraquark states. The predicted masses M Zb c (1 +− ) = 7.30 ± 0.08 GeV and M Zb c (1 ++ ) = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 70 publications
3
54
0
Order By: Relevance
“…(24), and we determine the corresponding k n cot δ 0 (k n ) using Eq. (26). We parametrize the scattering amplitude using the effective-range expansion (ERE),…”
Section: B Effective-range Expansion and Determination Of The Bound-mentioning
confidence: 99%
“…(24), and we determine the corresponding k n cot δ 0 (k n ) using Eq. (26). We parametrize the scattering amplitude using the effective-range expansion (ERE),…”
Section: B Effective-range Expansion and Determination Of The Bound-mentioning
confidence: 99%
“…Furthermore, it will be very easy to distinguish the all-heavy tetraquark states from the states which have been observed because their masses should be far away from the mass regions of the observed states. Thus, besides some previous works on the heavy tetraquark states [12][13][14][15][16][17], many new studies have been carried out in recent years [11,[18][19][20][21][22][23][24][25][26][27][28][29][30], although some of the conclusions are quite different from each other. In some works, it is predicted that there exist stable bound tetraquark cccc states and/or bound tetraquark bbbb states with relatively smaller masses below the thresholds of heavy charmonium pairs [11,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…as a powerful constraint to satisfy. In previous works, we observed that the energy scale formula can enhance the pole contribution remarkably for the tetraquark (molecular) states and pentaquark (molecular) states [13,14,23,28,29]. Now let us optimize the continuum threshold parameter s 0 and choose the best Borel parameter T 2 via trial and error, and finally obtain the Borel window, the continuum threshold parameter, the best energy scale of the QCD spectral density, and the pole contribution, which are shown in Table 1.…”
Section: Qcd Sum Rules For the Triply-charmed Hexaquark Statesmentioning
confidence: 91%
“…In the QCD sum rules for the tetraquark (molecular) states, pentaquark (molecular) states and hexaquark states (or dibaryon states), we take into the vacuum condensates, which are vacuum expectations of the quark-gluon operators of the order O(α k s ) with k ≤ 1 in a consistent way [12,13,14,23,24,25,28,29]. In the present case, if take the truncation k ≤ 1, the highest dimensional vacuum condensates are qq 3 αsGG π and qq qg s σGq 2 , the vacuum condensates αsGG π qq 2 qg s σGq , g 3 s GGG qq 3 and qg s σGq 3 come from the quark-gluon operators of the order O(α 3 2 s ) and should be discarded.…”
Section: Qcd Sum Rules For the Triply-charmed Hexaquark Statesmentioning
confidence: 99%
See 1 more Smart Citation